(untitled) (Fiep Bulletin - online, 2012)
New ideas have emerged in the context of Physical Education in Brazil since the eighties of last century, suggesting that physical education needed in crisis, to justify itself and seek their identity. After a few years, ideas that justified the crisis are still observable. The Human Motricity Science presents itself as a proposal for overcoming the crisis in question, since she appears in the context of a paradigmatic crisis in Science, a new paradigm in which the Man, Science and Society can only be understood in the look of complexity. However, the complex paradigm cannot completely exclude the processes and modes of thought of previous paradigm, but proposes a new world view. Similarly, the Human Motricity Science cannot replace what has been proposed so far for Physical Education, or give up the whole construction of knowledge produced, but allows for changes. The Human Motricity Science proposes an epistemological break, a change in the way of seeing the area in all its aspects. The object of study for Physical Education is the physical, because physical education itself has its origin in a science guided by fragmentation. The object of study of Human Motricity Science is Man in search of transcendence, and that Man is a being in the world, only one, indivisible, showing the relationship between man and society and culture. While emerging Science, Human Motricity is in the process of building its methods and its pedagogy, but the teaching as a complex process, the human being as a unit complex and multidimensional, the meaning and significance of what is taught and human praxis, can be considered as guiding principles of an action under the new teaching paradigm.